The effects and costs of home-based rehabilitation for heart failure with reduced ejection fraction: The REACH-HF multicentre randomized controlled trial. (February 2019) - Dalal, Hasnain M; Taylor, Rod S; Jolly, Kate; Davis, Russell C; Doherty, Patrick; Miles, Jackie; van Lingen, Robin; Warren, Fiona C; Green, Colin; Wingham, Jennifer; Greaves, Colin; Sadler, Susannah; et al.
Background: Cardiac rehabilitation improves health-related quality of life (HRQoL) and reduces hospitalizations in patients with heart failure, but international uptake of cardiac rehabilitation for heart failure remains low. Design and methods: The aim of this multicentre randomized trial was to compare the REACH-HF (Rehabilitation EnAblement in CHronicHeart Failure) intervention, a facilitated self-care and home-based cardiac rehabilitation programme to usual care for adults with heart failure with reduced ejection fraction (HFrEF). The study primary hypothesis was that the addition of the REACH-HF intervention to usual care would improve disease-specific HRQoL (Minnesota Living with Heart Failure questionnaire (MLHFQ)) at 12 months compared with usual care alone. Results: The study recruited 216 participants, predominantly men (78%), with an average age of 70 years and mean left ventricular ejection fraction of 34%. Overall, 185 (86%) participants provided data for the primary outcome. At 12 months, there was a significant and clinically meaningful between-group difference in the MLHFQ score of –5.7 points (95% confidence interval –10.6 to –0.7) in favour of the REACH-HF intervention group ( p  = 0.025). With the exception of patient self-care ( p  < 0.001) there was no significant difference in other secondary outcomes, including clinical events ( p  > 0.05) at follow-up compared with usual care. The mean cost of the REACH-HF intervention was £418 per participant. Conclusions: The novel REACH-HF home-based facilitated intervention for HFrEF was clinically superior in disease-specific HRQoL at 12 months and offers an affordable alternative to traditional centre-based programmes to address current low cardiac rehabilitation uptake rates for heart failure.